The experience of the illness and of the treatment for the person with systemic arterial hypertension: an ethnographic study - Silvana Maria Coelho Leite Fava; Marcia Maria Fontao Zago; Maria Suely Nogueira; Eliza Maria Rezende Dazio (Universidade de São Paulo, 2013)
OBJECTIVE: to interpret the meanings of the experience of the condition and of the treatment among people with arterial hypertension. METHOD: the authors adopted the frames of reference of interpretive and medical anthropology and of the ethnographic method. 22 people with arterial hypertension, and 10 Family Health Strategy health workers, all from Minas Gerais, participated. The authors used interviews, participant observation, focus groups, field diaries and analysis of medical records. Ethical precepts were respected. RESULTS: two nuclei of meaning emerged: "The condition as an expression of way of living", and "The perspective of the cure of the condition". Nervous problems represent the nosological and symptomatic categories, caused by the urban way of living. The participants are supported by the belief of the curing of the problem. The family, spirituality and religion constitute social support networks. The therapeutic routes interpenetrate for the cure of the problem. The 'folk' health subsystem constitutes an important route because it provides better well-being and remission of the symptoms. CONCLUSION: the gaps evidenced between the points of view of the health professionals and the interviewees allow one to re-think the praxis so as to provide comprehensive, contextualized and humanized care, which encourages the people's potential for living, for empowerment, and for self-care.